A multiphase dietetic protocol incorporating an improved ketogenic diet enhances weight loss and alters the gut microbiome of obese people. (17th February 2022) - Yuan, Weiwei; Lu, Wenwei; Wang, Hongchao; Wu, Wenjun; Zhou, Qunyan; Chen, Yutao; Lee, Yuan Kun; Zhao, Jianxin; Zhang, Hao; Chen, Wei
Abstract: The prevalence of obesity and its associated diseases is increasing. In the current study, 15 obese subjects took part in a 12-week multiphase dietetic protocol incorporating an improved ketogenic diet (MDP-i-KD) (KYLLKS 201806). We investigated the effects of the MDP-i-KD on the anthropometric parameters and the gut microbiota of obese subjects. Our results showed that the MDP-i-KD led to significant reductions in body mass index in obese subjects. The MDP-i-KD significantly decreased the relative abundance of the Lachnospiraceae_ND3007_group, the Eubacterium_hallii_group, and Pseudomonas and Blautia . In addition, gut microbiota co-occurrence networks in obese subjects were restructured to a more healthy condition after weight loss. These results show that the MDP-i-KD enhanced weight loss, which may be associated with dietary-induced changes in the gut microbiome. Our results emphasise the importance of determining the interaction between the host and microbial cells to comprehensively understand the mechanism by which diet affects host physiology and the microbiota.